Contextual Estimation of Marketable and Marketed Surplus of Selected Seasonal Fruits: A Study Based on Chittagong Hill Tracts (CHT) of Bangladesh - Islam, Md Jahurul (International Journal of Sustainable Agricultural Research, 2019)
This study is an attempt to assess the marketable and marketed surplus of selected seasonal fruits (mango, jackfruit, and litchi) in the Chittagong hill tracts of Bangladesh. Primary data were used for the study. In total, 459 sample fruit growers were selected purposively for the study. Proportionate random sampling was followed in case of selecting the sampling unit. It was apparent to interpret from the survey that in case of mango production, 78% fruit grower planted Rangui variety whereas Amrapali was ranked second highest (36%) including the eight groups of Bandarban and Rangamati of the survey. Among the three mentioned varieties of litchi, BARI litchi 2 variety was more prevalent (21%) than the other varieties. Also 69% respondent grew jackfruit whereas the average production was more in Rangamati than in Bandarban area. It is more apparent for all three of the seasonal fruits that, the marketable surplus was found to be higher than the net marketed surplus. That means farmer retains more for their consumption and other uses than the actual amount marketed. Running factor analysis, several cases were found that affect sustainable market linkage which was categorized into four factors like marketing, economic, social and environmental factor and the KMO value was found to be 0.527, generally, indicate that a factor analysis might be useful with this data. This study recommends increasing the marketed surplus with the increase of marketable surplus so that it can ultimately help fruit grower to link themselves with the market and increase their revenue.